Estudo do potencial terapêutico da maitenina em células de câncer de colo uterino - Galiardi, Ana Emília Brumatti [UNESP] (2015)
Cervical cancer is a worldwide public health problem, especially in developing countries, setting the fourth most common female cancer in the world. The infection by human papillomavirus (HPV) is the main risk factor for the development of this cancer, being present in 90% of cases of cervical cancer in the world population. Forward the search for new chemotherapeutic agents, natural products have strongly contributed to the identification of these substances and the development of modern therapeutics. Maytenin is a quinonemethide triterpene extracted from the roots of Maytenus ilicifolia plant, which has some biological activities previously reported as an antifungal, antiprotozoal and especially antitumor action. At the moment there are no reports in the literature relating the activity of maytenin in infected cells by HPV-16. The aim of this study was to evaluate the cytotoxicity of maytenin in cervical carcinoma line infected by HPV-16 (SiHa), non-infected by the virus (C-33 A) and by immortalized human keratinocytes (HaCaT), as well as verifying the induction of apoptosis and / or necrosis by Hoechst test and propidium iodide and the induction of apoptosis by caspase-3 activity in all three cell lines, in addition to check for changes in the cell cycle of treated cells with maytenin and the potential of genotoxicity and mutagenicity, and to evaluate the proliferation of the three cell lines. The cytotoxicity assay was performed by sulforhodamine B method and the three cell lines were treated during 6, 12 or 24 hours. It was possible to observe a concentration effect and response time in three lines analyzed. The IC50 was 3,26, 8,49 and 3,09 μM for SiHa, C-33 A and HaCaT lines respectively, in 24 hours treatment time. In order to evaluate the potential inductive effect of apoptosis it was performed a marking cytomorphological test with Hoechst and propidium iodide in 6 and 12 hours treatment times, and for the three cell lines it was ...